Clinical Outcomes of Stereotactic Body Radiotherapy for Patients with Lung Tumors in the State of Oligo-Recurrence. (8th July 2012) - Inoue, Tetsuya; Katoh, Norio; Onimaru, Rikiya; Shirato, Hiroki
Abstract : We retrospectively evaluated the clinical outcomes of patients with oligometastatic lung tumors who underwent stereotactic body radiotherapy (SBRT). Twenty-two patients with one or two oligometastatic lung tumors were treated with SBRT at our institution between 1999 and 2009. With a median follow-up period of 25 months from the date of SBRT to the detection of oligometastatic lung tumors, the patients' 3- and 5-year overall survival (OS) and progression-free survival (PFS) rates were 72% and 54%, respectively. The median disease-free interval (DFI) between the treatment of the primary site and SBRT to oligometastatic lung tumors was 41 months. The OS of patients with a DFI ≥ 36 months was significantly longer than that of the patients with a DFI < 36 months by the log-rank test (P = 0.02 ). For patients with a DFI ≥ 36 months, the 3- and 5-year OS rates were both 88%, compared to 50% for the patients with a DFI < 36 months. The primary tumor of all patients was locally controlled when SBRT to oligometastatic lung tumors was performed, and thus they were in the state of "oligo-recurrence." Patients with oligometastatic lung lesions treated by SBRT had good prognoses. This was especially true of the patients with a long DFI and in the state of "oligo-recurrence."